2023
DOI: 10.1097/pas.0000000000002098
|View full text |Cite
|
Sign up to set email alerts
|

Sweat Gland Tumors Arising on Acral Sites

Abstract: Recurrent oncogenic drivers have been identified in a variety of sweat gland tumors. Recently, integration of human papillomavirus type 42 (HPV42) has been reported in digital papillary adenocarcinoma (DPA). The main objectives of the present study were (i) to provide an overview of the prevalence of previously identified oncogenic drivers in acral sweat gland tumors and (ii) to genetically characterize tumors in which no recurrent genetic alteration has been identified yet. Cases of acral sweat gland tumors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, the evaluation of NUT expression in skin tumours in several independent studies [15][16][17]47 confirmed the high specificity of NUT expression for the diagnosis of poroma and porocarcinoma, but also allowed identification of a new tumour entity, i.e. NUT adnexal carcinoma, [19][20][21]99 an extremely rare tumour that will be mentioned as a provisional tumour entity in the 5th WHO classification of cutaneous tumours.…”
Section: Association Between Yap1 Fusion Type Histology and Prognosismentioning
confidence: 78%
See 2 more Smart Citations
“…Interestingly, the evaluation of NUT expression in skin tumours in several independent studies [15][16][17]47 confirmed the high specificity of NUT expression for the diagnosis of poroma and porocarcinoma, but also allowed identification of a new tumour entity, i.e. NUT adnexal carcinoma, [19][20][21]99 an extremely rare tumour that will be mentioned as a provisional tumour entity in the 5th WHO classification of cutaneous tumours.…”
Section: Association Between Yap1 Fusion Type Histology and Prognosismentioning
confidence: 78%
“…So far, only four cases with either BRD3:: NUTM1 or NSD3::NUTM1 fusions have been published. 19,20,99 One case with BRD3::NUTM2B may belong to the same spectrum. 21 So far no primary cutaneous tumour with BRD4::NUTM1 fusion has been identified.…”
Section: Association Between Yap1 Fusion Type Histology and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, five cases of primary cutaneous NUT carcinomas have been reported with BRD3::NUTM1 , BRD3::NUTM2B , and NSD3::NUTM1 rearrangements 4–7 . Interestingly, these tumors morphologically show an eccrine ductal and follicular infundibular phenotype in contrast to the typical poorly differentiated phenotype of extracutaneous NUT carcinomas 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with results indicating that 13/14 of poroid hidradenomas showed NUT-1 expression. 4 Recently, Kervarrec et al 7 reported YAP-1-NUTM1 fusion in 3 of 3 cases of poroid hidradenoma at acral sites. The limited data available suggest that DPAC does not show NUT-1 staining.…”
mentioning
confidence: 99%